Optimizing Criminal Sanctions Against Children as Murder Perpetrators from the Perspective of Modern Punishment Objectives - Resa Ayuning Maharanti; Jawade Hafidz (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This research examines the effectiveness and optimization of criminal sanctions imposed on children who commit murder, using the framework of modern sentencing theory and Indonesia’s juvenile criminal justice system. The study adopts a normative juridical approach combined with judicial analysis of Court Decisions 12/Pid.Sus-Anak/2020/PN Jkt.Pst and 7/Pid.Sus-Anak/2025/PN Kka. The findings reveal that although the Juvenile Justice System Act emphasizes rehabilitation and the best interests of the child, the practical implementation remains less effective due to persistent punitive tendencies, limited rehabilitative facilities, and the absence of specific sentencing guidelines for juvenile offenders in serious crimes. Variations in judicial reasoning between the two decisions also indicate disparities, particularly in assessing psychological conditions, social background, culpability levels, and sentencing objectives. This study proposes an integrative model for optimizing juvenile sentencing through individualized assessments, enhanced institutional capacity of juvenile correctional facilities, harmonized sentencing guidelines, and strengthened restorative justice values. Such an approach ensures that sentencing aligns with the rehabilitative and preventive aims of modern penology while still upholding societal justice.